2019
DOI: 10.1002/ese3.339
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale pore structure and fractal characteristics of the continental Yanchang Formation Chang 7 shale in the southwestern Ordos Basin, central China

Abstract: Shales from the Yanchang Formation Chang 7 Member in the Ordos Basin are among the most important shale reservoirs in China and have been investigated due to their great potential. Knowledge of pore structure is important for understanding the storage capacity and flow mechanism in shale reservoirs. In this study, eight shale samples were collected from the Yanchang Formation Chang 7 Member in the southwestern Ordos Basin, and their geochemistry, mineral compositions, pore structure, and fractal characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…According to petrophysical test results, the shale physical model can be simplified into two parts: mineralogical components and pore space (Figure b). Mineralogical components include brittle minerals (quartz, feldspar, carbonate minerals, and pyrite), clay minerals, and dispersed organic matter, ,, in which organic matter and clay minerals are regarded as the main carriers for shale gas adsorption. ,,, Pore space covers the pores and fractures developed within and between various minerals. ,,, Some pores are isolated, which the fluids (formation water, liquid hydrocarbon, and gas) cannot access. , In the accessible pore space, with the subtraction of the fraction occupied by formation water and oil, the remaining is the available space for shale gas storage in the form of adsorbed gas and free gas.…”
Section: Resultsmentioning
confidence: 99%
“…According to petrophysical test results, the shale physical model can be simplified into two parts: mineralogical components and pore space (Figure b). Mineralogical components include brittle minerals (quartz, feldspar, carbonate minerals, and pyrite), clay minerals, and dispersed organic matter, ,, in which organic matter and clay minerals are regarded as the main carriers for shale gas adsorption. ,,, Pore space covers the pores and fractures developed within and between various minerals. ,,, Some pores are isolated, which the fluids (formation water, liquid hydrocarbon, and gas) cannot access. , In the accessible pore space, with the subtraction of the fraction occupied by formation water and oil, the remaining is the available space for shale gas storage in the form of adsorbed gas and free gas.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al (2017) studied the pore structures of Chang 7 tight sandstones using HPMI combined with fractal theory, and the value of calculated fractal dimensions changes from 2.2520 to 2.7875. Ju et al (2019) studied the pore structure and fractal characteristics of Chang 7 shale were combined with N 2 GA, and found that the fractal dimensions increase with the increase in organic matter and clay mineral content.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Atomic-scale geometrically heterogeneous surfaces: statistical self-similarity, a typical geometric feature of surface heterogeneity that can hardly be described by Euclidean geometry, is a ubiquitous characteristic of most materials in nature . Thanks to the fractal theory advanced by Mandelbrot, , the surface fractal dimension functions as an applicable measure of surface geometric heterogeneity. The fractal pore morphology has been examined by mercury intrusion porosimetry (MIP), the fractal Frenkel–Halsey–Hill (FHH) adsorption isotherm equation based on nitrogen adsorption, , nuclear magnetic resonance, ,, small-angle and ultrasmall-angle neutron scattering, , ...…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate marked surface geometric heterogeneity at the atomic scale. (2) Slitlike shape: the pore shape can be determined from the shape of the hysteresis loop of the nitrogen adsorption and desorption isotherms (see refs , , , , , , , , , , , , , , , , ) according to the classification by the International Union of Pure and Applied Chemistry (IUPAC) or by the field emission scanning electron microscope (see refs , , , , , , , , , , , , , , , , , , , , , , ) and MIP. ,,, The summary statistics reveal that slit pores constitute the largest...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation